PERAN GURU MENTOR DALAM FACILITATING LEARNING BAGI MAHASISWA PGSD SAAT PRAKTEK PENGALAMAN LAPANGAN 1 - Ashiong Parhehean Munthe (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2016)
The purpose of this research was to describe the role of teachers mentors that is facilitating learning for Primary School Teacher Education students (PGSD) Universitas Pelita Harapan when implementing First Field Experience (PPL 1) program. The implementation of the learning process through PPL 1 for student teachers, was strongly influenced by the role of the mentors teachers. The role teachers mentors to help, to be a role model, to do assessment and to give feedback to students teacher facilitate the students and increase their abilities to understand the whole lesson held at school. The role of teachers mentors were expected to have an influence on students in the second PPL, third PPL, and in other learning activities in campus. The research method applied in this research is descriptive qualitative method in which it will describe the results of student assessment to their teachers mentors when in PPL 1. The assessment is a questionnaire with a range of 1 to 5. The statements in the questionnaire were taken from a field experience handbook of Faculty of Education (Teachers College) Universitas Pelita Harapan about the roles and responsibilities of a teachers mentors. The participants involved in this research were PGSD students. The result is, according to the students, the teachers mentors, have done facilitating learning in PPL 1.Keywords : Teachers Mentors, Facilitating Learning, PPL 1, Observations, Reflections